Sytuacja polityczna w Polsce w latach 1944–1947 w świetle „Biuletynu Wolnej Polski” – pisma Związku Patriotów Polskich na Środkowym Wschodzie - Pietrzak, Jacek (Przegląd Nauk Historycznych, 2008)
During World War II communists organized some political groups in Polish Army on Middle East as well as among Polish civilian war refugees in Palestine. On the beginning of 1944 Związek Patriotów Polskich na Środkowym Wschodzie (Polish Patriots' Association on the Middle East) was founded with strong support from Palestinian Communist Party. The organization was very active in propaganda and it published its own paper "Biuletyn Wolnej Polski" ("Bulletin of Free Poland") from March 1944 to May 1947. Articles published in the Bulletin tried to discredit Polish Government in Exile and Polish Underground State and they gave a false picture of Poland ruled by communists as "democratic" and "normal" country. Communists were eager to make a political confusion among Polish exiles. After the War they persuaded Polish war refugees to return to Poland, because a mass home-coming would be a great success of communist propaganda. Among authors of the Bulletin there were some very intelligent and well-educated publicists who tried to avoid traditional communist slogans. However Palestine was not easy field for their activity, because most of refugees had a very strong anti-communist attitude and many of them had had tragic experiences in Soviet Union earlier in the War.